Neutral meson properties under an external magnetic field in nonlocal chiral quark models - Gómez Dumm, Daniel Alberto (2018)
We study the behavior of neutral meson properties in the presence of a static uniform external magnetic field in the context of nonlocal chiral quark models. The formalism is worked out introducing Ritus transforms of Dirac fields, which allow to obtain closed analytical expressions for π⁰ and σ meson masses and for the π⁰ decay constant. Numerical results for these observables are quoted for various parametrizations. In particular, the behavior of the π⁰ meson mass with the magnetic field is found to be in good agreement with lattice QCD results. It is also seen that the Goldberger-Treiman and Gell-Mann-Oakes-Renner chiral relations remain valid within these models in the presence of the external magnetic field.